An Evaluation of the COVID-19 Pandemic and Perceived Social Distancing Policies in Relation to Planning, Selecting, and Preparing Healthy Meals: An Observational Study in 38 Countries Worldwide - De Backer, Charlotte; Teunissen, Lauranna; Cuykx, Isabelle; Decorte, Paulien; Pabian, Sara; Gerritsen, Sarah; Matthys, Christophe; Al Sabbah, Haleama; Van Royen, Kathleen; , the Corona Cooking Survey Study Group (Frontiers in Nutrition, 2021)
Objectives To examine changes in planning, selecting, and preparing healthy foods in relation to personal factors (time, money, stress) and social distancing policies during the COVID-19 crisis. Methods Using cross-sectional online surveys collected in 38 countries worldwide in April-June 2020 (N = 37,207, Mage 36.7 SD 14.43, 73.6% women), we compared changes in food literacy behaviors to changes in personal factors and social distancing policies, using hierarchical multiple regression analyses controlling for sociodemographic variables. Results Increases in planning (4.7 SD 1.2, 4.9 SD 1.3), selecting (3.8 SD 1.7, 3.8 SD 1.7), and preparing (4.6 SD 1.3, 4.7 SD 1.3) healthy foods were found for women and men, and positively related to perceived time availability among women and stay-at-home policies for planning and preparing in women. Psychological distress was a barrier for women, and an enabler for men. COVID-19 induced financial stress was a barrier depending on various sociodemographic variables (all p < 0.01). Conclusion Stay-at-home policies and feelings of having more time during COVID-19 seem to have improved food literacy among women. Stress and other social distancing policies relate to food literacy in more complex ways, highlighting the necessity of a health equity lens.